Animating the Body in Museum Exhibitions of Fashion and Dress. (May 2015) - Mida, Ingrid
Abstract : Clothing takes form and is animated by the body. Within the context of a museum, present-day practice standards limit the options for displays of dress artifacts to static dress forms and mannequins. This was not always the case, and at one time museums routinely used live models for runway presentations and for photography of dress artifacts. This paper considers the history of the use of live models in the display of dress artifacts in museums and examines novel curatorial strategies employed to create the illusion of an animated body in some recent notable museum exhibitions of fashion.